Reviving Gandhian Educational Principles through Local Artisanal Practices: A Case Study of Vocational Learning in Baramulla, Jammu and Kashmir, India - Zubaida Ahad (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study explores the integration of Gandhian educational principles within the artisanal practices of Baramulla, a culturally rich district in Jammu and Kashmir, India. Grounded in the Nai Talim philosophy, which emphasizes the synthesis of productive manual labor with intellectual growth, this research investigates 15 diverse artisan-led units, including handloom weavers, potters, blacksmiths, and herbal medicine preparers. These units, deeply embedded in local economies and cultural traditions, serve as organic learning environments where skills are transmitted through observation, repetition, and intergenerational mentorship. Adopting a participatory ethnographic methodology, the study utilized immersive fieldwork, unstructured interviews, and skill mapping to capture the nuanced processes of knowledge transfer and resource utilization. The findings reveal that these artisanal units exemplify Gandhian ideals such as self-reliance, ecological sustainability, and dignity of labor, while simultaneously addressing contemporary challenges like youth unemployment, rural depopulation, and economic marginalization. However, the research also identifies critical barriers, including the lack of formal recognition, inadequate financial support, and disconnect from mainstream educational frameworks, which hinder the full potential of these traditional knowledge systems. In the context of the National Education Policy (NEP) 2020, which calls for experiential learning and vocational education, this study argues for the systemic integration of such artisanal practices into formal curricula. By doing so, it envisions a transformative educational model that not only preserves cultural heritage but also promotes sustainable development, social equity, and community resilience.